Crystal structure of bis(μ2-diethyldithiocarbamato-κ3S,S′:S′)-bis(tricyclohexylphosphane-κP)dicopper(I), C46H86Cu2N2P2S4 - Tan, Yi Jiun *; Yeo, Chien Ing *; Halcovitch, Nathan R.; Tiekink, Edward R. T. * (De Gruyter Open Access, 2018)
C46H86Cu2N2P2S4, triclinic, P¯1 (no. 2), a=9.9626(3) Å, b=11.0489(3) Å, c=12.3604(3) Å, α=106.205(3)°, β=99.165(2)°, γ=100.306(3)°, V =1253.53(6) Å3, Z =1, Rgt(F)=0.0232, wRref(F2)=0.0555, T =100(2) K.